Germany - Weller, Marc-Philippe; Hübner, Leonhard; Kaller, Luca (Private international law aspects of corporate social responsibility, 2020)
This chapter provides an overview on how Private International Law (PIL) may be made useful for the purposes of Corporate Social Responsibility (CSR) under German Law.After briefly glancing at the institutional framework of CSR in Germany (“Definition and Sources”), we analyse which rules of the substantive law may be used to protect CSR considerations (“Characterisation”). To this end, we take a closer look at company law, contract law and the law of tort. Within the company law, extending the duty of legality (Legalitätspflicht), piercing the corporate veil (Durchgriffshaftung) or using the newly introduced sections 289b and 289c of the German Commercial Code (HGB) may be options for enforcing CSR-rules. It would, however, be preferable to recognise a duty of care of the parent company within the law of tort, i.e. recognise its tortious responsibility across the value chain.We summarise alternative methods of dispute resolution within CSR cases (“Alternative methods of dispute resolution”). The subsequent chapters evaluate under which circumstances German courts will have jurisdiction to decide CSR cases (“Jurisdiction”) as well as which law will be applicable in relation to company structure (lex societatis), contract law and the law of tort (“Applicable law”). Within the law of tort, we suggest that victims of human rights violations should be able to choose the law applicable to their case under the Rome II regulation. In the final chapter, we outline the requirements for recognising and enforcing foreign judgments (“Recognition and enforcement of judgments”).